Організаційно-правове та психологічне забезпечення гендерної рівності в діяльності органів внутрішніх справ України та правоохоронних органів зарубіжних країн - Смірнова, О. М.; Smirnova, O. M. (Вісник Одеського національного університету імені І. І. Мечникова. Серія : Психологія. - 2014. - № 2. - С. 298-306, 2014)
Статтю присвячено дослідженню організаційно-правового та психологічного забезпечення гендерної рівності в діяльності органів внутрішніх справ України та правоохоронних органів зарубіжних країн. Визначено позитивний досвід організаційно-правового та психологічного забезпечення гендерної рівності та дотримання прав жінок-поліцейських в діяльності правоохоронних органів зарубіжни країни та діагностовано сучасний стан зазначеної проблематики в Україні.

The article is dedicated to the review of the actual problem i. e. organizationally legal and psychological maintenance of gender equality in the activities of the bodies of internal Affairs in Ukraine and law enforcement agencies of foreign countries. The positive experience of foreign countries has been analyzed in the research and overcoming the problem of gender discrimination in the work of police. In particular the foreign research finds, that women bring in the work of police certain habits and strong sides i.e. minimize the force use, due to their psychological sides, police women better settle the violence situations and more affectively working with the victims of violence etc. It is said that taking into account of positive foreign experience in organizationally legal and psychological maintenance of gender equality in the activities of the bodies of internal Affairs in Ukraine will allow increase the efficiency of personnel potential and the share of women who serve in the law enforcement agencies and that is the necessary measure for increasing the quality of operational activities.

Статья посвящена исследованию организационно-правового и психологического обеспечения гендерного равенства в деятельности органов внутренних дел Украины и правоохранительных органов зарубежных стран. Определен положительный опыт организационно-правового и психологического обеспечения гендерного равенства и соблюдения прав женщин-полицейских в деятельности правоохранительных органов зарубежной страны и диагностировано современное состояние указанной проблематики в Украине.
Organizationally legal and psychological maintenance of gender equality in the activities of the bodies of internal affairs in Ukraine and law enforcement agencies of foreign countries
Keywords: гендерна рівність; gender equality; гендерное равенство; органи внутрішніх справ; law enforcement bodies; органы внутренних дел; організаційно-правове забезпечення; organizational and legal support; организационно-правовое обеспечение; психологічне забезпечення; psychological support; психологическое обеспечение; зарубіжний досвід; foreign experience; зарубежный опыт